Silicon carbon-graphite negative electrode active material, negative electrode material and application of silicon carbon-graphite negative electrode active material

By using a combination of spherical silicon carbon material and fast-charging artificial graphite in the negative electrode material of lithium-ion batteries, the volume expansion and contraction problem of silicon-based anode material during charging and discharging is solved, and the battery performance of high energy density and low expansion is achieved.

CN119786577AActive Publication Date: 2025-04-08EVE ENERGY CO LTD

Patent Information

Application Number
CN202412000133.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing silicon-based negative electrode materials have serious volume expansion and contraction problems during the charging and discharging of lithium-ion batteries, resulting in cracking and falling off of materials, affecting battery capacity and life.

Method used

The silicon-carbon-graphite negative electrode active material composed of spherical silicon-carbon materials and fast-charge artificial graphite is used to improve the compaction density and cycle stability of the negative electrode sheet through the synergistic effect of the spherical silicon-carbon materials and the fast-charge artificial graphite.

Benefits of technology

It significantly improves the energy density and circulation performance of lithium-ion batteries, reduces the expansion rate, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786577A_ABST
    Figure CN119786577A_ABST
Patent Text Reader

Abstract

The invention provides a silicon carbon-graphite negative electrode active material, a negative electrode material and application of the silicon carbon-graphite negative electrode active material. The silicon carbon-graphite negative electrode active material comprises a spherical silicon carbon material and fast-charging artificial graphite. The silicon-carbon-graphite negative electrode active material contains the spherical silicon-carbon material, on one hand, the energy density of the negative electrode active material is improved by the spherical silicon-carbon material, on the other hand, the spherical silicon-carbon material is spherical and can improve the pressure resistance, and the spherical silicon-carbon material and the fast-charging artificial graphite have a synergistic effect, so that the energy density of the negative electrode active material is improved. The silicon carbon-graphite negative electrode active material composed of the spherical silicon carbon material and the fast-charging artificial graphite has relatively high pressure resistance, so that the compaction density of a negative electrode plate prepared from the silicon carbon-graphite negative electrode active material can be greatly improved, and the negative electrode plate shows more excellent long-cycle low-expansion performance under the same compaction; therefore, the silicon carbon-graphite negative electrode active material has excellent expansion inhibition performance while the energy density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a silicon-carbon-graphite negative electrode active material, in particular to a silicon-carbon-graphite negative electrode active material, a negative electrode material and applications thereof. Background Art

[0002] Lithium-ion batteries are widely used in smart phones, laptops, bicycles, and automobiles. With the development of science and technology, the requirements for energy density are gradually increasing, and silicon-based negative electrode materials have emerged. The advantages of silicon material negative electrodes are mainly reflected in their high theoretical specific capacity and excellent performance to lithium voltage. The theoretical specific capacity of silicon materials is significantly higher than that of graphite, which is approaching its performance limit. This makes silicon materials likely to become the preferred negative electrode materials for high energy density lithium batteries. Secondly, the voltage platform of silicon materials is slightly higher than that of graphite, and it is difficult to cause surface lithium deposition during charging. Therefore, its safety performance is also better than that of graphite negative electrode materials.

[0003] However, both silicon-oxygen and silicon-carbon materials will experience severe volume expansion and contraction (up to 300%) during the battery charging and discharging process. During the battery charging and discharging process, the high expansion rate makes the material extremely prone to cracking and falling off, resulting in battery capacity loss and battery failure.

[0004] Therefore, the application of silicon oxygen and / or silicon carbon materials in the prior art is mostly mixed in the graphite negative electrode to improve the energy density. Based on this, in order to alleviate the volume expansion of the silicon-based negative electrode during the charging and discharging process, the matching of the negative electrode formula is particularly important. The silicon carbon materials currently used in the market are mostly amorphous morphology, and the selection of graphite is also a single consideration of the rate and expansion. In terms of binders, polyacrylic acid, carboxymethyl cellulose, and styrene-butadiene rubber are more selected. However, the expansion inhibition effect of the negative electrode active materials disclosed in the prior art is very limited.

[0005] CN116314605A discloses a negative electrode plate for a lithium-ion battery, a preparation method thereof, and a lithium-ion battery. The negative electrode plate for the lithium-ion battery has a composite layer structure, including a first layer, a second layer, and a third layer. The first layer is close to the current collector side, and the third layer is far away from the current collector, wherein: the first layer includes a graphite negative electrode active material and a silicon-based active negative electrode material; the second layer includes a graphite negative electrode active material, a silicon-based active negative electrode material, and conductive carbon; and the third layer is composed of a graphite negative electrode material.

[0006] CN104810506A discloses a high energy density lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an outer package. The positive electrode sheet and the negative electrode sheet are respectively composed of a positive current collector and a negative current collector and positive and negative electrode materials coated on the positive current collector and the negative current collector. The positive electrode material comprises a positive electrode active substance, a positive electrode conductive agent and a positive electrode binder. The negative electrode material comprises a negative electrode active substance, a negative electrode conductive agent, a thickener and a negative electrode binder. The positive electrode active substance adopts a nickel-cobalt-aluminum ternary positive electrode material or a nickel-cobalt-manganese ternary positive electrode material, and the negative electrode active substance adopts a silicon-carbon material in which a carbon source is coated with a silicon source.

[0007] The silicon-based negative electrode active materials disclosed in the prior art all have certain defects, and there is a problem that they cannot have a high energy density and good expansion inhibition performance. Therefore, it is very important to develop and design a new type of silicon-carbon-graphite negative electrode active material, negative electrode material and its application. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a silicon-carbon-graphite negative electrode active material, a negative electrode material and its application. The silicon-carbon-graphite negative electrode active material provided by the present invention contains spherical silicon-carbon material. On the one hand, the spherical silicon-carbon material improves the energy density of the negative electrode active material. On the other hand, the spherical silicon-carbon material has a spherical morphology, which can improve the compressive resistance. Moreover, the spherical silicon-carbon material has a synergistic effect with fast-charging artificial graphite. Therefore, the silicon-carbon-graphite negative electrode active material composed of the spherical silicon-carbon material and the fast-charging artificial graphite has a high compressive resistance, which can greatly improve the compaction density of the negative electrode sheet prepared with the silicon-carbon-graphite negative electrode active material, so that the negative electrode sheet exhibits more excellent long-cycle low expansion performance under the same compaction; therefore, the silicon-carbon-graphite negative electrode active material has excellent expansion inhibition performance while improving the energy density.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a silicon-carbon-graphite negative electrode active material, wherein the silicon-carbon-graphite negative electrode active material comprises a spherical silicon-carbon material and fast-charging artificial graphite.

[0011] The silicon-carbon-graphite negative electrode active material provided by the present invention contains spherical silicon-carbon material. On the one hand, the spherical silicon-carbon material improves the energy density of the negative electrode active material. On the other hand, the spherical silicon-carbon material has a spherical morphology, which can improve the compressive resistance. Moreover, the spherical silicon-carbon material has a synergistic effect with the fast-charging artificial graphite. Therefore, the silicon-carbon-graphite negative electrode active material composed of the spherical silicon-carbon material and the fast-charging artificial graphite has a high compressive resistance, which can greatly improve the compaction density of the negative electrode sheet prepared with the silicon-carbon-graphite negative electrode active material, so that the negative electrode sheet exhibits more excellent long-cycle low expansion performance under the same compaction; therefore, the silicon-carbon-graphite negative electrode active material has excellent expansion inhibition performance while improving the energy density.

[0012] Preferably, the D50 particle size of the spherical silicon-carbon material is smaller than the D50 particle size of the fast-filling artificial graphite.

[0013] Due to the "crosstalk" effect of lithium ions between silicon and graphite; lithium ions will gradually accumulate inside silicon during the cycle; under the repeated squeezing of the huge expansion stress of silicon particles, the capacity of graphite will decrease. Therefore, in the present invention, by limiting the D50 particle size of the spherical silicon-carbon material to be smaller than the D50 particle size of the fast-charging artificial graphite, the pores formed between the fast-charging artificial graphite particles are made equivalent to the size of the spherical silicon-carbon material after expansion, and the pores formed between the fast-charging artificial graphite particles are used to accommodate the volume change of the spherical silicon-carbon material, thereby improving the expansion inhibition performance of the silicon-carbon-graphite negative electrode active material.

[0014] Preferably, the D50 particle size of the spherical silicon-carbon material is 9 to 10 μm, for example, it can be 9 μm, 9.1 μm, 9.2 μm, 9.3 μm, 9.4 μm, 9.5 μm, 9.6 μm, 9.7 μm, 9.8 μm, 9.9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the silicon content in the spherical silicon-carbon material is 47.5-55%, for example, it can be 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 51%, 52% or 55%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the compaction density of the spherical silicon carbon material is 1.2 to 1.7 g / cm 3 , for example, it can be 1.7 g / cm 3 、1.68g / cm 3 , 1.66g / cm 3 , 1.64g / cm 3 、1.62g / cm 3 , 1.6g / cm3 , 1.55g / cm 3 , 1.5g / cm 3 , 1.45g / cm 3 , 1.4g / cm 3 , 1.3g / cm 3 or 1.2g / cm 3 , but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the spherical silicon-carbon material has a charge capacity of 1650 to 1850 mAh at a voltage of 1.5 V, for example, it may be 1650 mAh, 1660 mAh, 1665 mAh, 1670 mAh, 1680 mAh, 1690 mAh, 1700 mAh, 1720 mAh, 1750 mAh, 1800 mAh or 1850 mAh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] The button cell capacity of the spherical silicon-carbon material described in the present invention is defined as: a button cell manufacturing method is adopted, and the formula of the button cell manufacturing method contains polyacrylic acid (PAA), carbon nanotubes (CNT), conductive carbon black (SP), spherical silicon-carbon material and water. After sufficient stirring, it is coated on a copper foil, and after drying and rolling, it is sliced ​​into a mold to obtain a disc with a diameter of 14 mm. It is assembled according to conventional button cell steps. After the assembly of the button cell is completed, it is allowed to stand for 6 hours, and then the gram capacity and initial efficiency are tested.

[0019] The test method for gram capacity is: discharge to 0.005V with a current of 0.05C, let it stand for 5 minutes, then discharge to 0.005V with a current of 0.01C, let it stand for 5 minutes, and then charge to 1.5V with a current of 0.05C. The test results show that the charging capacity divided by the mass of the effective active substance is the gram capacity of the material (1.5V).

[0020] Preferably, the first efficiency of the spherical silicon-carbon material at a voltage of 0.8 V is 82-84%. The first efficiency may be, for example, 82%, 82.5%, 83%, 83.5% or 84%, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0021] The test method for the first effect is: discharge the button-type battery to 0.005V at a current of 0.05C, let it stand for 5 minutes, then discharge it to 0.005V at a current of 0.01C, let it stand for 5 minutes, and then charge it to 0.8V at a current of 0.05C. The test shows that the ratio of the button-type charging capacity to the discharge capacity is the first effect of the button-type battery at a voltage of 0.8V.

[0022] Preferably, the spherical silicon-carbon material is prepared by a gas phase method.

[0023] Preferably, the vapor phase method comprises: using a resin material as a carbon matrix and preparing a spherical silicon-carbon material by vapor phase deposition.

[0024] Preferably, the pore volume of the carbon matrix is ​​≥ 0.8 cm 3 / g, and the proportion of pore diameters greater than 2nm is ≥93%.

[0025] The pore volume of the carbon matrix in the present invention is ≥ 0.8 cm 3 / g, for example, 0.8 cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 1cm 3 / g, 1.05cm 3 / g, 1.1cm 3 / g, 1.15cm 3 / g or 1.2cm 3 / g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] The proportion of pores in the carbon matrix described in the present invention that are larger than 2 nm is ≥ 93%, for example, it can be 93%, 93.5%, 94%, 94.5%, 95, 95.5%, 96%, 96.5%, 97%, 97.5% or 98%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the D50 particle size of the fast-charging artificial graphite is 12 to 14 μm, for example, it may be 12 μm, 12.2 μm, 12.4 μm, 12.6 μm, 12.8 μm, 13 μm, 13.2 μm, 13.4 μm, 13.6 μm, 13.8 μm or 14 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the compaction density of the fast-filling artificial graphite is 1.73-1.78 g / cm 3 , for example, it can be 1.73 g / cm 3 , 1.74g / cm 3 , 1.75g / cm 3 , 1.76g / cm 3 , 1.77g / cm 3 or 1.78 g / cm 3 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the gram capacity of the fast-charging artificial graphite is 356 to 360 mAh / g, for example, it can be 356 mAh / g, 357 mAh / g, 358 mAh / g, 359 mAh / g or 360 mAh / g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the orientation degree OI value of the fast-charging artificial graphite is 6.0-9.0, for example, it can be 9.0, 8.8, 8.6, 8.2, 8.0, 7.8, 7.5, 7.2, 7.0, 6.5 or 6.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the fast-charging artificial graphite can meet the high-rate fast-charging performance of 3C or above.

[0032] Preferably, the method for preparing the fast-charging artificial graphite comprises:

[0033] The raw material of petroleum coke is crushed and shaped, and then semi-finished secondary particles are obtained by granulation. The obtained semi-finished secondary particles are subjected to graphitization heat treatment, and then coated with a coating agent and then subjected to carbonization heat treatment to obtain fast-filling artificial graphite.

[0034] Preferably, the particle size of the petroleum coke is 6-7 μm, and the tap density is greater than 0.68 g / cm 3 .

[0035] The particle size of the petroleum coke green coke described in the present invention is 6-7μm, for example, it can be 6μm, 6.1μm, 6.2μm, 6.3μm, 6.4μm, 6.5μm, 6.6μm, 6.7μm, 6.8μm, 6.9μm or 7μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the pulverization and shaping obtains pulverized particles with a D50 particle size of 7 to 9 μm, for example, it can be 7 μm, 7.2 μm, 7.4 μm, 7.6 μm, 7.8 μm, 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm or 9 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the granulation comprises: mixing an asphalt binder with the crushed particles, and performing granulation at 800-950° C. for less than 9 hours.

[0038] In the present invention, granulation is carried out at 800-950°C, for example, it can be 800°C, 820°C, 850°C, 870°C, 890°C, 910°C, 930°C or 950°C, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In the present invention, the granulation time is less than 9 hours, for example, it can be 8.9 hours, 8.7 hours, 8.5 hours, 8 hours, 7.5 hours, 7 hours, 6.5 hours, 6 hours, 5.5 hours or 5 hours, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the granulation is carried out in a granulation axe.

[0041] Preferably, the D50 particle size of the semi-finished secondary particles obtained after the granulation is 12 to 13.5 μm, for example, it can be 12 μm, 12.2 μm, 12.4 μm, 12.6 μm, 12.8 μm, 13 μm, 13.2 μm, 13.4 μm or 13.5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the temperature of the graphitization heat treatment is 2850-3200° C., the time is 9-12 hours, and a graphitized material is obtained after the graphitization heat treatment.

[0043] The temperature of the graphitization heat treatment in the present invention is 2850-3200°C, for example, it can be 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C, 3150°C or 3200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] The time of the graphitization heat treatment in the present invention is 9 to 12 hours, for example, it can be 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the coating agent includes a combination of at least two of a phenolic resin, an epoxy resin and a tubular conductive agent, and typical but non-limiting combinations include a combination of a phenolic resin and an epoxy resin, a combination of an epoxy resin and a tubular conductive agent, or a combination of a phenolic resin, an epoxy resin and a tubular conductive agent.

[0046] Preferably, the coating method comprises mixing the coating agent and the graphitized material by stirring.

[0047] Preferably, the stirring is carried out in a horizontal reactor.

[0048] Preferably, based on the total mass of the coating agent and the graphitized material, the mass fraction of the coating agent is not less than 8wt%, for example, it can be 8wt%, 8.2wt%, 8.5wt%, 8.8wt%, 9wt%, 9.2wt%, 9.5wt%, 9.8wt% or 10wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the carbonization heat treatment is carried out at a temperature of 900 to 1100° C. and for a time of 7 to 9 hours.

[0050] The temperature of the carbonization heat treatment in the present invention is 900-1100°C, for example, it can be 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] The time of the carbonization heat treatment in the present invention is 7 to 9 hours, for example, it can be 7.2 hours, 7.5 hours, 7.8 hours, 8 hours, 8.2 hours, 8.5 hours, 8.8 hours or 9 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, based on the mass of the silicon-carbon-graphite negative electrode active material, the mass fraction of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 3-15wt%, and the mass fraction of the fast-charging artificial graphite is 85-97wt%.

[0053] In the present invention, the mass fraction of the silicon-carbon-graphite negative electrode active material is 3-15wt%, for example, 3wt%, 5wt%, 7wt%, 10wt%, 12wt%, 14wt% or 15wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In the present invention, taking the mass of the silicon-carbon-graphite negative electrode active material as 100%, the mass fraction of the fast-charging artificial graphite is 85-97wt%, for example, it can be 85wt%, 86wt%, 87wt%, 88wt%, 90wt%, 92wt%, 95wt% or 97wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In a second aspect, the present invention provides a negative electrode material, which includes a conductive agent, a binder and the silicon-carbon-graphite negative electrode active material described in the first aspect.

[0056] Preferably, the binder comprises lithiated polyacrylic acid and styrene-butadiene rubber.

[0057] The lithiated polyacrylic acid in the binder of the present invention contains hydrophilic side chains and lipophilic groups, realizing the combination of multiple functions; the molecular chain conformation can be changed according to pH, and the viscosity of the system increases rapidly after the molecular chain is stretched, so that carboxymethyl cellulose can be replaced to play the role of thickening, suspension, bonding and dispersion; in addition, the lithiated polyacrylic acid, as a macromolecular lithium salt thickener, has better dispersibility on graphite, and lithium carboxylate can provide lithium ion channels, which is beneficial to the transmission of lithium ions, reduces the internal resistance of the battery, and improves the dynamic performance.

[0058] The binder in the present invention includes styrene-butadiene rubber, and the styrene-butadiene rubber emulsion can be directly prepared into slurry by adding alkali in a wet process, which is not easy to gel, can simplify the process and improve the efficiency.

[0059] Preferably, the solid content of the lithiated polyacrylic acid is 0.5-2.5wt%, for example, it can be 0.5wt%, 0.7wt%, 0.9wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt%, 1.9wt%, 2wt%, 2.2wt% or 2.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] Preferably, the conductive agent includes any one of carbon black, carbon nanotubes, carbon nanofibers or graphene, or a combination of at least two of them. Typical but non-limiting combinations include a combination of carbon black and carbon nanotubes, a combination of carbon nanotubes and carbon nanofibers, a combination of carbon nanofibers and graphene, or a combination of carbon nanotubes, carbon nanofibers and graphene.

[0061] Preferably, the viscosity of the binder is 10000-20000 mPa·s, the glass transition temperature is 90-95° C., and the mass ratio of lithiated polyacrylic acid to styrene-butadiene rubber in the binder is (2-4):(1-3).

[0062] The viscosity of the adhesive in the present invention is 10000-2000 mPa·s, for example, it can be 10000 mPa·s, 11000 mPa·s, 12000 mPa·s, 13000 mPa·s, 14000 mPa·s, 15000 mPa·s, 16000 mPa·s, 17000 mPa·s, 18000 mPa·s, 19000 mPa·s or 20000 mPa·s, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0063] The glass transition temperature of the binder in the present invention is 90-95°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] The mass ratio of lithiated polyacrylic acid to styrene-butadiene rubber in the binder of the present invention is (2-4):(1-3), for example, it can be 2:1, 2:1.3, 2:1.7, 2:1.9, 2:2.3, 2:2.7, 2:2.9, 2:3, 4:1, 4:1.3, 4:1.7, 4:1.9, 4:2.3, 4:2.7, 4:2.9 or 4:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] Preferably, based on the mass of the negative electrode material, the mass fraction of the conductive agent in the negative electrode material is 1-2wt%, the mass fraction of the binder is 3-4wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material is 94-96wt%.

[0066] In the present invention, the mass fraction of the negative electrode material is 1-2wt%, and the mass fraction of the conductive agent in the negative electrode material is 1wt%, for example, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In the present invention, the mass fraction of the negative electrode material is 3-4wt%, and the mass fraction of the binder in the negative electrode material is 3wt%, for example, 3wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt% or 4wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In the present invention, the mass fraction of the negative electrode material is 94-96wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material in the negative electrode material is 94wt%, for example, 94wt%, 94.2wt%, 94.6wt%, 94.8wt%, 95wt%, 95.2wt%, 95.4wt%, 95.6wt%, 95.8wt% or 96wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In a third aspect, the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, wherein the negative electrode material layer is composed of the negative electrode material described in the second aspect.

[0070] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.

[0071] Preferably, the positive electrode plate of the lithium-ion battery comprises a positive electrode collector and a positive electrode material layer covering the surface of the positive electrode collector, and the positive electrode active material in the positive electrode material layer comprises any one of a ternary positive electrode material, lithium cobalt oxide or lithium iron phosphate, or a combination of at least two of them.

[0072] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0073] Compared with the prior art, the present invention has the following beneficial effects:

[0074] (1) The silicon-carbon-graphite negative electrode active material provided by the present invention includes spherical silicon-carbon material. On the one hand, the spherical silicon-carbon material improves the energy density of the negative electrode active material. On the other hand, the spherical silicon-carbon material has a spherical morphology, which can improve the compressive strength. Moreover, the spherical silicon-carbon material has a synergistic effect with the fast-charging artificial graphite. Therefore, the silicon-carbon-graphite negative electrode active material composed of the spherical silicon-carbon material and the fast-charging artificial graphite has a high compressive strength, thereby greatly improving the compaction density of the negative electrode sheet prepared with the silicon-carbon-graphite negative electrode active material, so that the negative electrode sheet exhibits a more excellent long-cycle low expansion performance under the same compaction; therefore, the silicon-carbon-graphite negative electrode active material has excellent expansion inhibition performance while improving the energy density;

[0075] (2) In the present invention, the D50 particle size of the spherical silicon-carbon material is limited to be smaller than the D50 particle size of the fast-charging artificial graphite, so that the pores formed between the fast-charging artificial graphite particles are equivalent to the size of the spherical silicon-carbon material after expansion, and the pores formed between the fast-charging artificial graphite particles are used to accommodate the volume change of the spherical silicon-carbon material, thereby improving the expansion inhibition performance of the silicon-carbon-graphite negative electrode active material;

[0076] (3) The lithiated polyacrylic acid in the binder of the present invention contains hydrophilic side chains and lipophilic groups, realizing a combination of multiple functions; the molecular chain conformation can be changed according to pH, and the viscosity of the system increases rapidly after the molecular chain is stretched, which can replace carboxymethyl cellulose and play the role of thickening, suspension, bonding and dispersion; in addition, the lithiated polyacrylic acid, as a macromolecular lithium salt thickener, has better dispersibility on graphite, and the lithium carboxylate can provide lithium ion channels, which is beneficial to the transmission of lithium ions, reducing the internal resistance of the battery and improving the dynamic performance;

[0077] (4) The binder in the present invention includes styrene-butadiene rubber, and the styrene-butadiene rubber emulsion can be directly prepared into slurry by adding alkali using a wet process. It is not easy to gel, which can simplify the process and improve efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 It is 1.2g / cm 3 SEM image of spherical silicon-carbon material at compaction density.

[0079] Figure 2 It is 1.2g / cm 3 SEM image of amorphous silicon-carbon material at compaction density. DETAILED DESCRIPTION

[0080] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0081] Example 1

[0082] This embodiment provides a silicon-carbon-graphite negative electrode active material, wherein the silicon-carbon-graphite negative electrode active material comprises spherical silicon-carbon material and fast-charging artificial graphite;

[0083] Taking the mass of the silicon-carbon-graphite negative electrode active material as 100%, the mass fraction of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 10wt%, and the mass fraction of the fast-charging artificial graphite is 90wt%.

[0084] The D50 particle size of the spherical silicon-carbon material is 9.5 μm, the silicon content is 50%, and the compacted density is 1.2 g / cm 3 , the buckle capacity at 1.5V is 1700mAh, and the first efficiency at 0.8V is 83%;

[0085] The method for preparing spherical silicon-carbon material is:

[0086] The pore volume is 0.9 cm 3 / g and 95% of the pore size is greater than 2nm. The spherical silicon-carbon material is prepared by vapor deposition.

[0087] The D50 particle size of the fast-charging artificial graphite is 13 μm, and the compacted density is 1.76 g / cm 3 , the gram capacity is 358 mAh / g, and the orientation degree OI value is 8.0;

[0088] The method for preparing the fast-charging artificial graphite is:

[0089] The particle size is 6.5 μm and the tap density is 0.7 g / cm 3The raw petroleum coke is used as raw material for crushing and shaping to obtain crushed particles with a D50 particle size of 7.5 μm, the asphalt binder is mixed with the obtained crushed particles, and granulated in a granulating axe at 880°C for 6 hours to obtain semi-finished secondary particles with a D50 particle size of 12.5 μm, the obtained semi-finished secondary particles are subjected to graphitization heat treatment at 3000°C for 10 hours to obtain graphitized material, and then phenolic resin and the obtained graphitized material are mixed by stirring in a horizontal reactor (the mass fraction of the phenolic resin is 10wt% based on the total mass of the phenolic resin and the graphitized material), and then carbonized at 1000°C for 7 hours to obtain fast-filling artificial graphite.

[0090] This embodiment also provides a negative electrode material, which includes carbon black, a binder and the silicon-carbon-graphite negative electrode active material provided in this embodiment;

[0091] The mass fraction of carbon black in the negative electrode material is 1.5wt%, the mass fraction of the binder is 3.5wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material is 95wt%;

[0092] The binder includes lithiated polyacrylic acid and styrene-butadiene rubber in a mass ratio of 3:2. The viscosity of the binder is 15000 mPa·s and the glass transition temperature is 92°C.

[0093] This embodiment further provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, and the negative electrode material layer is composed of the negative electrode material provided in this embodiment.

[0094] Example 2

[0095] This embodiment provides a silicon-carbon-graphite negative electrode active material, wherein the silicon-carbon-graphite negative electrode active material comprises spherical silicon-carbon material and fast-charging artificial graphite;

[0096] Taking the mass of the silicon-carbon-graphite negative electrode active material as 100%, the mass fraction of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 3wt%, and the mass fraction of the fast-charging artificial graphite is 97wt%.

[0097] The spherical silicon-carbon material has a D50 particle size of 10 μm, a silicon content of 47.5%, and a compacted density of 1.2 g / cm 3 , the buckle capacity at 1.5V is 1850mAh, and the first efficiency at 0.8V is 84%;

[0098] The method for preparing spherical silicon-carbon material is:

[0099] The pore volume is 0.8 cm 3 / g and 93% of the pore size is greater than 2nm. The spherical silicon-carbon material is prepared by vapor deposition.

[0100] The D50 particle size of the fast-charging artificial graphite is 14 μm, and the compacted density is 1.78 g / cm 3 , the gram capacity is 360mAh / g, and the orientation degree OI value is 9.0;

[0101] The method for preparing the fast-charging artificial graphite is:

[0102] The particle size is 7 μm and the tap density is 0.88 g / cm 3 The raw petroleum coke is used as raw material for crushing and shaping to obtain crushed particles with a D50 particle size of 9 μm, the asphalt binder is mixed with the obtained crushed particles, and granulated in a granulating axe at 800°C for 8.5 hours to obtain semi-finished secondary particles with a D50 particle size of 13.5 μm, the obtained semi-finished secondary particles are subjected to graphitization heat treatment at 3200°C for 9 hours to obtain graphitized material, and then epoxy resin and the obtained graphitized material are mixed by stirring in a horizontal reactor (the mass fraction of the epoxy resin is 8wt% based on the total mass of the epoxy resin and the graphitized material), and then carbonized heat treatment is carried out at 900°C for 9 hours to obtain fast-filling artificial graphite.

[0103] This embodiment also provides a negative electrode material, which includes carbon nanotubes, a binder and the silicon-carbon-graphite negative electrode active material provided in this embodiment;

[0104] The mass fraction of carbon nanotubes in the negative electrode material is 2wt%, the mass fraction of the binder is 4wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material is 94wt%;

[0105] The binder comprises lithiated polyacrylic acid and styrene-butadiene rubber in a mass ratio of 2:3, the viscosity of the binder is 10000 mPa·s, and the glass transition temperature is 90°C.

[0106] This embodiment further provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, and the negative electrode material layer is composed of the negative electrode material provided in this embodiment.

[0107] Example 3

[0108] This embodiment provides a silicon-carbon-graphite negative electrode active material, wherein the silicon-carbon-graphite negative electrode active material comprises spherical silicon-carbon material and fast-charging artificial graphite;

[0109] Taking the mass of the silicon-carbon-graphite negative electrode active material as 100%, the mass fraction of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 15wt%, and the mass fraction of the fast-charging artificial graphite is 85wt%.

[0110] The D50 particle size of the spherical silicon-carbon material is 9 μm, the silicon content is 55%, and the compacted density is 1.2 g / cm 3 , the buckle capacity is 1650mAh at 1.5V voltage, and the first efficiency is 82% at 0.8V voltage;

[0111] The method for preparing spherical silicon-carbon material is:

[0112] The pore volume is 1.0 cm 3 / g and 97% of the pore size is greater than 2nm. The spherical silicon-carbon material is prepared by vapor deposition.

[0113] The D50 particle size of the fast-charging artificial graphite is 12 μm, and the compacted density is 1.73 g / cm 3 , the gram capacity is 356 mAh / g, and the orientation degree OI value is 6.0;

[0114] The method for preparing the fast-charging artificial graphite is:

[0115] The particle size is 6 μm and the tap density is 0.7 g / cm 3 The raw petroleum coke is crushed and shaped as raw material to obtain crushed particles with a D50 particle size of 7 μm, the asphalt binder is mixed with the obtained crushed particles, and granulated in a granulating axe at 950°C for 6 hours to obtain semi-finished secondary particles with a D50 particle size of 12 μm, the obtained semi-finished secondary particles are subjected to graphitization heat treatment at 2850°C for 12 hours to obtain graphitized material, and then phenolic resin and the obtained graphitized material are mixed by stirring in a horizontal reactor (the mass fraction of the phenolic resin is 12wt% based on the total mass of the phenolic resin and the graphitized material), and then carbonized at 1100°C for 7 hours to obtain fast-filling artificial graphite.

[0116] This embodiment also provides a negative electrode material, which includes graphene, a binder and the silicon-carbon-graphite negative electrode active material provided in this embodiment;

[0117] The mass fraction of graphene in the negative electrode material is 1wt%, the mass fraction of the binder is 3wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material is 96wt%;

[0118] The binder comprises lithiated polyacrylic acid and styrene-butadiene rubber in a mass ratio of 4:1, the viscosity of the binder is 20000 mPa·s, and the glass transition temperature is 95°C.

[0119] This embodiment further provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, and the negative electrode material layer is composed of the negative electrode material provided in this embodiment.

[0120] Example 4

[0121] This embodiment provides a silicon-carbon-graphite negative electrode active material, and the silicon-carbon-graphite negative electrode active material is the same as that in Embodiment 1.

[0122] This embodiment provides a negative electrode material, which is the same as Example 1 except that the binder in the negative electrode material is replaced with an equal mass of a binder composed of carboxymethyl cellulose, polyacrylic acid (solid content of 5%, viscosity of 15000mPa.s) and styrene-butadiene rubber in a mass ratio of 1:1:1.

[0123] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0124] Example 5

[0125] This embodiment provides a silicon-carbon-graphite negative electrode active material, and the silicon-carbon-graphite negative electrode active material is the same as that in Embodiment 1.

[0126] This embodiment provides a negative electrode material, which is the same as that of Embodiment 1 except that the lithiated polyacrylic acid in the binder of the negative electrode material is replaced with carboxymethyl cellulose of the same mass.

[0127] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0128] Example 6

[0129] This embodiment provides a silicon-carbon-graphite negative electrode active material, which is the same as that of Embodiment 1 except that the D50 particle size of the fast-charging artificial graphite in the silicon-carbon-graphite negative electrode active material is 8 μm.

[0130] This embodiment further provides a negative electrode material, which is the same as that of Embodiment 1 except that the silicon-carbon-graphite negative electrode active material in the negative electrode material is the silicon-carbon-graphite negative electrode active material provided in this embodiment.

[0131] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0132] Example 7

[0133] This embodiment provides a silicon-carbon-graphite negative electrode active material, which is the same as that of Embodiment 1 except that the D50 particle size of the fast-charging artificial graphite in the silicon-carbon-graphite negative electrode active material is 16 μm.

[0134] This embodiment further provides a negative electrode material, which is the same as that of Embodiment 1 except that the silicon-carbon-graphite negative electrode active material in the negative electrode material is the silicon-carbon-graphite negative electrode active material provided in this embodiment.

[0135] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0136] Example 8

[0137] This embodiment provides a silicon-carbon-graphite negative electrode active material, which is the same as that of Embodiment 1 except that the D50 particle size of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 7 μm.

[0138] This embodiment further provides a negative electrode material, which is the same as that of Embodiment 1 except that the silicon-carbon-graphite negative electrode active material in the negative electrode material is the silicon-carbon-graphite negative electrode active material provided in this embodiment.

[0139] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0140] Example 9

[0141] This embodiment provides a silicon-carbon-graphite negative electrode active material, which is the same as that of Embodiment 1 except that the D50 particle size of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 12 μm.

[0142] This embodiment further provides a negative electrode material, which is the same as that of Embodiment 1 except that the silicon-carbon-graphite negative electrode active material in the negative electrode material is the silicon-carbon-graphite negative electrode active material provided in this embodiment.

[0143] This embodiment further provides a negative electrode plate, which is the same as that of Embodiment 1 except that the negative electrode material layer of the negative electrode plate is composed of the negative electrode material provided in this embodiment.

[0144] Comparative Example 1

[0145] This comparative example provides a silicon-carbon-graphite negative electrode active material, except that the spherical silicon-carbon material is replaced by an amorphous silicon-carbon material, the amorphous silicon-carbon material has a D50 particle size of 9.5 μm, a silicon content of 50%, and a compacted density of 1.5 g / cm 3Except that the buckling capacity is 1750mAh at 1.5V and the first efficiency is 83% at 0.8V, the rest are the same as those in Example 1.

[0146] This comparative example also provides a negative electrode material, which is the same as Example 1 except that the silicon-carbon-graphite negative electrode active material in the negative electrode material is the silicon-carbon-graphite negative electrode active material provided in this comparative example.

[0147] This comparative example also provides a negative electrode plate, which is the same as Example 1 except that the negative electrode material layer of the negative electrode plate has the negative electrode material composition provided in this comparative example.

[0148] Comparative Example 2

[0149] This comparative example provides a silicon-carbon-graphite negative electrode active material, except that the spherical silicon-carbon material is replaced by an amorphous silicon-carbon material, the amorphous silicon-carbon material has a D50 particle size of 9.5 μm, a silicon content of 50%, and a compacted density of 1.5 g / cm 3 Except that the buckling capacity at 1.5V is 1750mAh and the first efficiency at 0.8V is 83%, the rest are the same as those in Example 1.

[0150] This comparative example provides a negative electrode material, which is the same as Example 1 except that the silicon-carbon-graphite negative electrode active material is replaced by the silicon-carbon-graphite negative electrode active material in this comparative example, and the binder in the negative electrode material is replaced by an equal mass of a binder composed of polyacrylic acid (solid content of 5%, viscosity of 15000mPa.s), carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1:1.

[0151] This comparative example also provides a negative electrode plate, which is the same as Example 1 except that the negative electrode material layer of the negative electrode plate has the negative electrode material composition provided in this comparative example.

[0152] At 1.2 g / cm 3 At a compaction density of , the morphology of spherical silicon-carbon material and amorphous silicon-carbon material was tested using a scanning electron microscope. The SEM images of the spherical silicon-carbon material obtained by the test are as follows: Figure 1 As shown, the SEM image of amorphous silicon carbon material is as follows Figure 2 shown; through Figure 1 and Figure 2 By comparison, it can be seen that at 1.2g / cm 3At a compaction density of , the amorphous silicon-carbon material has cracked particles, while the spherical silicon-carbon material has no cracked particles. The spherical silicon-carbon material has a spherical morphology, and the spherical silicon-carbon material can improve the compressive resistance. Therefore, the silicon-carbon-graphite negative electrode active material composed of the spherical silicon-carbon material and the fast-charging artificial graphite has a high compressive resistance, which can greatly improve the compaction density of the negative electrode sheet prepared with the silicon-carbon-graphite negative electrode active material, so that the negative electrode sheet exhibits more excellent long-cycle low expansion performance under the same compaction.

[0153] The negative electrode sheet provided in the above embodiment and comparative example is used to prepare a lithium ion battery. The method for preparing the lithium ion battery is as follows: the obtained lithium cobalt oxide positive electrode material, conductive carbon black SP and polyvinylidene fluoride PVDF are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone is used as a solvent. The mixture is mixed and stirred into a slurry. The obtained slurry is evenly coated on an aluminum foil with a scraper with a coating gap of 100 um; after coating, it is first blown and dried, and then rolled to prepare a sheet; the negative electrode sheet provided in the embodiment and comparative example of the present invention is used as the negative electrode, the ceramic coated microporous membrane is used as the diaphragm, and the high-voltage silicon-based electrolyte is used as the electrolyte. The positive electrode sheet, the negative electrode sheet, the diaphragm and the electrolyte are assembled to obtain a lithium ion battery;

[0154] The 3C charging cross-current ratio, energy density, full-charge expansion rate and cycle performance of the obtained lithium-ion battery were tested;

[0155] The test method of 3C charging cross-current ratio is: perform battery cell test in Xinwei cabinet, perform constant current fast charging at 3C current, test to obtain the charging capacity and total charging capacity in the constant current stage, 3C charging cross-current ratio = charging capacity in the constant current stage / total charging capacity, the test results are shown in Table 1;

[0156] The test method of energy density is: the total electric energy density of lithium battery = battery discharge energy / battery weight; the test method of discharge energy: charge to 4.5V at 0.2C constant current and constant voltage, and then discharge to 2.5V at 0.2C, cycle for 3 weeks, and obtain the discharge energy. The total electric energy density is calculated as shown in Table 1, and the test results are shown in Table 1;

[0157] The test method of the full-charge expansion rate is: test to obtain the initial thickness of the negative electrode sheet before charging, and the full-charge thickness after full charge, the full-charge expansion rate = (full-charge thickness of the negative electrode sheet - initial thickness of the negative electrode sheet) / initial thickness of the negative electrode sheet, the test results are shown in Table 1;

[0158] The test method for cycle performance is as follows: at an ambient temperature of 25°C, constant current and constant voltage charging is performed at the same rate of 3C, the cut-off voltage is 3.65V, the cut-off current is 0.05C, and the battery is left for 30 minutes. The battery is discharged at a constant current of 1C and the cut-off voltage is 2.5V. The battery is cycled for 600 cycles according to the above test method. The capacity retention rate and expansion rate of the battery are shown in Table 2. Then, at an ambient temperature of 45°C, constant current and constant voltage charging is performed at the same rate of 3C, the cut-off voltage is 3.65V, the cut-off current is 0.05C, and the battery is left for 30 minutes. The battery is discharged at a constant current of 1C and the cut-off voltage is 2.5V. The battery is cycled for 600 cycles according to the above test method. The capacity retention rate and expansion rate of the battery are shown in Table 2.

[0159] Table 1

[0160]

[0161] Table 2

[0162]

[0163]

[0164] From Table 1, we can get:

[0165] (1) The lithium-ion battery prepared with the negative electrode materials provided in Examples 1 to 3 has a higher 3C charging cross-current ratio, a higher energy density and a lower full-charge expansion rate; in addition, the lithium-ion battery prepared with the negative electrode materials provided in Examples 1 to 3 exhibits a higher capacity retention rate and a lower expansion rate in the cycle performance test;

[0166] (2) By comparing Example 1 with Examples 4 and 5, it can be seen that the binder in the negative electrode material provided by the present invention affects the performance of the lithium ion battery; when the binder is a binder composed of lithiated polyacrylic acid and styrene butadiene rubber, the lithium ion battery exhibits more excellent performance, which is because: first, the lithiated polyacrylic acid in the binder contains hydrophilic side chains and lipophilic groups, realizing the combination of multiple functions; the molecular chain conformation can be changed according to pH, and the viscosity of the system increases rapidly after the molecular chain is stretched, which can replace carboxymethyl cellulose to play the role of thickening, suspension, bonding and dispersion; in addition, lithiated polyacrylic acid, as a macromolecular lithium salt thickener, has better dispersibility on graphite, and lithium carboxylate can provide lithium ion channels, which is beneficial to the transmission of lithium ions, reduces the internal resistance of the battery, and improves the dynamic performance; second, the binder in the present invention includes styrene butadiene rubber, and the styrene butadiene rubber emulsion can be directly prepared into slurry by adding alkali using a wet process, which is not easy to gel, can simplify the process and improve efficiency; third, the binder composed of lithiated polyacrylic acid and styrene butadiene rubber replaces the traditional carboxymethyl cellulose, which effectively inhibits the expansion of the anode;

[0167] (3) By comparing Example 1 with Examples 6 and 7, it can be seen that the D50 particle size of the fast-charging artificial graphite in the silicon-carbon-graphite negative electrode active material of the present invention will affect the performance of the lithium-ion battery; when the D50 particle size of the fast-charging artificial graphite is 12 to 14 μm, the lithium-ion battery exhibits more excellent performance. This is because when the D50 particle size of the fast-charging artificial graphite is too small, it is not conducive to the performance of the fast-charging artificial graphite capacity, and the compressive strength is weak, resulting in the deterioration of the performance of the lithium-ion battery; when the D50 particle size of the fast-charging artificial graphite is too large, the lithium ion transmission path will increase, and the rate performance and fast charging performance will deteriorate;

[0168] (4) By comparing Example 1 with Examples 8 and 9, it can be seen that the D50 particle size of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material of the present invention will affect the performance of the lithium-ion battery; when the D50 particle size of the spherical silicon-carbon material is 9 to 10 μm, the lithium-ion battery exhibits more excellent performance. This is because when the D50 particle size of the spherical silicon-carbon material is too small, it will affect the initial effect of the lithium-ion battery and is not conducive to the improvement of energy density; when the D50 particle size of the spherical silicon-carbon material is too large, it is not conducive to the transmission of lithium ions, and the expansion rate after lithium insertion is relatively large;

[0169] (5) By comparing Example 1 with Comparative Example 1, it can be seen that the silicon-carbon-graphite negative electrode active material provided by the present invention contains spherical silicon-carbon material. On the one hand, the spherical silicon-carbon material improves the energy density of the negative electrode active material. On the other hand, the spherical silicon-carbon material has a spherical morphology, which can improve the compressive strength. Moreover, the spherical silicon-carbon material has a synergistic effect with the fast-charging artificial graphite. Therefore, the silicon-carbon-graphite negative electrode active material composed of the spherical silicon-carbon material and the fast-charging artificial graphite has a high compressive strength, which can greatly improve the compaction density of the negative electrode sheet prepared with the silicon-carbon-graphite negative electrode active material, so that the negative electrode sheet exhibits a more excellent long-cycle low expansion performance under the same compaction; therefore, the silicon-carbon-graphite negative electrode active material has excellent expansion inhibition performance while improving the energy density.

[0170] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A silicon-carbon-graphite negative electrode active material, characterized in that: The silicon-carbon-graphite negative electrode active material comprises spherical silicon-carbon material and fast-charging artificial graphite.

2. The silicon-carbon-graphite negative electrode active material according to claim 1, characterized in that: The D50 particle size of the spherical silicon-carbon material is smaller than the D50 particle size of the fast-filling artificial graphite.

3. The silicon-carbon-graphite negative electrode active material according to claim 1 or 2, characterized in that: The D50 particle size of the spherical silicon-carbon material is 9 to 10 μm; Preferably, the silicon content in the spherical silicon-carbon material is 47.5-55%; Preferably, the compaction density of the spherical silicon carbon material is 1.2 to 1.7 g / cm 3 ; Preferably, the spherical silicon-carbon material has a buckling capacity of 1650 to 1850 mAh at a voltage of 1.5 V; Preferably, the first efficiency of the spherical silicon-carbon material at a voltage of 0.8 V is 82-84%.

4. The silicon-carbon-graphite negative electrode active material according to any one of claims 1 to 3, characterized in that: The D50 particle size of the fast-charging artificial graphite is 12 to 14 μm; Preferably, the compacted density of the fast-filling artificial graphite is 1.73-1.78 g / cm 3 ; Preferably, the gram capacity of the fast-charging artificial graphite is 356-360 mAh / g; Preferably, the orientation degree OI value of the fast-filling artificial graphite is 6.0-9.

0.

5. The silicon-carbon-graphite negative electrode active material according to any one of claims 1 to 4, characterized in that: The method for preparing the fast-charging artificial graphite comprises: The raw petroleum coke is crushed and shaped, and then granulated to obtain semi-finished secondary particles, the obtained semi-finished secondary particles are subjected to graphitization heat treatment, and then coated with a coating agent and then subjected to carbonization heat treatment to obtain fast-filling artificial graphite; Preferably, the particle size of the petroleum coke is 6-7 μm, and the tap density is 0.68-1 g / cm 3 ; Preferably, the pulverizing and shaping obtains pulverized particles with a D50 particle size of 7 to 9 μm; Preferably, the granulation comprises: mixing the asphalt binder with the crushed particles, and granulating at 800-950° C. for less than 9 hours; Preferably, the D50 particle size of the semi-finished secondary particles obtained after the granulation is 12 to 13.5 μm; Preferably, the temperature of the graphitization heat treatment is 2850-3200°C, the time is 9-12h, and the graphitization material is obtained after the graphitization heat treatment; Preferably, the coating agent comprises a combination of at least two of phenolic resin, epoxy resin and tubular conductive agent; Preferably, the carbonization heat treatment is carried out at a temperature of 900 to 1100° C. and for a time of 7 to 9 hours.

6. The silicon-carbon-graphite negative electrode active material according to any one of claims 1 to 5, characterized in that: Taking the mass of the silicon-carbon-graphite negative electrode active material as 100%, the mass fraction of the spherical silicon-carbon material in the silicon-carbon-graphite negative electrode active material is 3-15wt%, and the mass fraction of the fast-charging artificial graphite is 85-97wt%.

7. A negative electrode material, characterized in that: The negative electrode material comprises a conductive agent, a binder and the silicon-carbon-graphite negative electrode active material according to any one of claims 1 to 6.

8. The negative electrode material according to claim 7, characterized in that The binder includes lithiated polyacrylic acid and styrene-butadiene rubber; Preferably, the viscosity of the binder is 10000-20000 mPa·s, the glass transition temperature is 90-95° C., and the mass ratio of lithiated polyacrylic acid to styrene-butadiene rubber in the binder is (2-4):(1-3); Preferably, based on the mass of the negative electrode material, the mass fraction of the conductive agent in the negative electrode material is 1-2wt%, the mass fraction of the binder is 3-4wt%, and the mass fraction of the silicon-carbon-graphite negative electrode active material is 94-96wt%.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, and the negative electrode material layer is composed of the negative electrode material according to claim 7 or 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • High-energy density lithium ion battery

    CN104810506A

  • Electrode material and secondary battery

    CN109704323A

  • Composite binder for silicon-carbon cathode material and preparation method of binder

    CN109728305A

  • Lithium ion battery with high energy density and charging capacity

    CN112310347A

  • Lithium ion battery silicon-carbon negative electrode material and preparation method thereof

    CN114388755A

Cited By

  • Composite negative electrode material, negative electrode sheet, electrochemical device and electronic equipment

    CN121748353A